Correlation between Serum Fibrinogen Level and Acute Ischemic Stroke Severity - Rambe, Avie Hanindya Dwiyanti; Batubara, Chairil Amin (CoinReads Media Prima, 2023)
Introduction: Indonesia still has a high burden for stroke, and stroke became the number one cause of mortality, in which the condition caused 328,5 thousand deaths (21,2% of death from all cause) in 2012 according to WHO. Until now, there are multiple parameters that can be used to determine the severity of an acute ischemic stroke event, one of the laboratory parameters being serum fibrinogen level. The aim of this study was to find the relationship between serum fibrinogen level and the severity of acute ischemic stroke. Method: The study used a cross-sectional design from acute ischemic stroke patients in the inpatient wards of H. Adam Malik Medan Hospital and network hospital. We used contingency coefficient correlation analysis test to determine the relationship between serum fibrinogen level and the severity of acute ischemic stroke. This study involved 40 acute ischemic stroke patients. Results: The results of statistical analysis found a significant positive correlation between serum fibrinogen level and acute ischemic stroke severity with weak correlation strength (p=0.028; r= 0.328) with the median NIHSS score of the subject 6,5 and median serum fibrinogen level being 320,9mg/dL (87 – 881mg/dL). Conclusion: There was a significant relation between serum fibrinogen level and acute ischemic stroke severity. The result of this study proved that a higher serum fibrinogen level is associated with increased stroke severity.